Disruption of the Snf1 Gene Enhances Cell Growth and Reduces the Metabolic Burden in Cellulase-Expressing and Lipid-Accumulating Yarrowia lipolytica - Wei, Hui; Wang, Wei; Knoshaug, Eric P.; Chen, Xiaowen; Van Wychen, Stefanie; Bomble, Yannick J.; Himmel, Michael E.; Zhang, Min (Frontiers in Microbiology, 2021)
Yarrowia lipolytica is known to be capable of metabolizing glucose and accumulating lipids intracellularly; however, it lacks the cellulolytic enzymes needed to break down cellulosic biomass directly. To develop Y. lipolytica as a consolidated bioprocessing (CBP) microorganism, we previously expressed the heterologous CBH I, CBH II, and EG II cellulase enzymes both individually and collectively in this microorganism. We concluded that the co-expression of these cellulases resulted in a metabolic drain on the host cells leading to reduced cell growth and lipid accumulation. The current study aims to build a new cellulase co-expressing platform to overcome these hinderances by 1) knocking out the sucrose non-fermenting 1 (Snf1) gene that represses the energetically expensive lipid and protein biosynthesis processes, and 2) knocking in the cellulase cassette fused with the recyclable selection marker URA3 gene in the background of a lipid-accumulating Y. lipolytica strain overexpressing ATP citrate lyase (ACL) and diacylglycerol acyltransferase 1 (DGA1) genes. We have achieved a homologous recombination insertion rate of 58% for integrating the cellulases-URA3 construct at the disrupted Snf1 site in the genome of host cells. Importantly, we observed that the disruption of the Snf1 gene promoted cell growth and lipid accumulation and lowered the cellular saturated fatty acid level and the saturated to unsaturated fatty acid ratio significantly in the transformant YL163t that co-expresses cellulases. The result suggests a lower endoplasmic reticulum stress in YL163t, in comparison to its parent strain Po1g ACL-DGA1. Furthermore, transformant YL163t increased in vitro cellulolytic activity by 30%, whereas the ‘total in vivo newly formed FAME (fatty acid methyl esters)’ increased by 16% in comparison to a random integrative cellulase-expressing Y. lipolytica mutant in the same YNB-Avicel medium. The Snf1 disruption platform demonstrated in this study provides a potent tool for the further development of Y. lipolytica as a robust host for the expression of cellulases and other commercially important proteins.